(untitled) (Multi-disciplinary Journal of Research and Development Perspectives, 2026)
Decentralisation of academic library brings about many gains which include; accessibility and proximity, ease of usage, relief and decongestion to central library, specialization, satisfaction of accreditation requirements, and standardization of service. Structure of decentralization in Nigeria university libraries include full, partial and mixed method of decentralization. Objects and structure of decentralization were also revealed in an exploratory analysis following system framework. Data used were entirely secondary. It was concluded that decentralization benefits cannot be derived without challenges in terms of cost, administrative difficulties, wastage and duplication, inadequate manpower, lack of physical space, facilities and security challenges. It was recommended that proprietors of public universities in Nigeria being the federal and state government should amend public university Acts and provide social policy framework in which benefits of decentralized academic library system will be achieved without destroying coordination, control and industrial harmony in terms of adopting full decentralization in small institutions and mixed method in complex institutions.